Net benefit and cost-effectiveness of universal iron-containing multiple micronutrient powders for young children in 78 countries: a microsimulation study - Sant-Rayn Pasricha, PhD; Adrian Gheorghe, PhD; Fayrouz Sakr-Ashour, MBBCh; Amrita Arcot, RDN; Lynnette Neufeld, PhD; Laura E Murray-Kolb, PhD; Parminder S Suchdev, ProfMD; Michael Bode, PhD (Elsevier, 2020)
Summary: Background: Universal home fortification of complementary foods with iron-containing multiple micronutrient powders (MNPs) is a key intervention to prevent anaemia in young children in low-income and middle-income countries. However, evidence that MNPs might promote infection raises uncertainty about whether MNPs give net health benefits and are cost-effective. We aimed to determined country-specific net benefit or harm and cost-effectiveness of universal provision of MNPs to children aged 6 months. Methods: We developed a microsimulation model to estimate net country-specific disability-adjusted life-years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) due to anaemia, malaria, and diarrhoea averted (or increased) by provision of a 6-month course of MNPs to children aged 6 months, compared with no intervention, who would be followed up for an additional 6 months (ie, to age 18 months). Anaemia prevalence was derived from Demographic and Health Surveys or similar national surveys, and malaria and diarrhoea incidence were sourced from the Global Burden of Disease Study. Programme and health-care costs were modelled to determine cost per DALY averted (US$). Additionally, we explored the effects of reduced MNP coverage in a sensitivity analysis. Findings: 78 countries (46 countries in Africa, 20 in Asia or the Middle East, and 12 in Latin America) were included in the analysis, and we simulated 5 million children per country. 6 months of universal distribution of daily MNPs, assuming 100% coverage, produced a net benefit (DALYs averted) in 54 countries (24 in Africa, 19 in Asia and the Middle East, 11 in Latin America) and net harm in 24 countries (22 in Africa, one in Asia, and one in Latin America). MNP intervention provided a benefit on YLDs associated with anaemia, but these gains were attenuated and sometimes reversed by increases in YLLs associated with malaria and diarrhoea, reducing the benefits seen for DALYs. In the 54 countries where MNP provision was beneficial, the median benefit was 28·1 DALYs averted per 10 000 children receiving MNPs (IQR 20·6-40·4), and median cost per DALY averted was $3576 (IQR 2474-4918). DALY effects positively correlated with moderate and severe anaemia prevalence in Asia, the Middle East, and Latin America, but correlated inversely in Africa. Suboptimal coverage markedly reduced DALYs averted and cost-effectiveness. Interpretation: Net health benefits of MNPs vary between countries, are highest where prevalence of moderate and severe anaemia is greatest but infection prevalence is smallest, and are ameliorated when coverage of the intervention is poor. Our data provide country-specific guidance to national policy makers. Funding: International Union of Nutrition Sciences.